Armed Forces in India's Northeast: A Necessity Review. (November 2015) - Ngaihte, Thangkhanlal
More than 60 years of de facto military rule through the Armed Forces (Special Powers) Act (AFSPA) 1958 in India's northeast has engendered neither stability nor peace. Problems regarding the impunity of violence and crime, official corruption and the virtual collapse of the rule of law continue, but the Act remains in operation. This article attempts to reframe the debates on the AFSPA in terms of its necessity by turning the necessity argument on its head and arguing that the secessionist insurgencies which were originally used to justify the Act have actually long ceased to exist. Since the principle of existential necessity that provided a fig leaf to the Act no longer applies, its continued application needs to be re-examined. It is further argued that the Indian military's increasing clout in internal security policy-making may have grave implications for Indian democracy itself, with negative impacts on the rule of law and in relation to safe inclusion strategies for India's northeast.